Scientific Inquiry and Nature of Science Implications for Teaching,Learning, and Teacher Education - Flick, Lawrence; Lederman, N.G (Contemporary Trends and Issues in Science Education,, 2006)
This book synthesizes the most current literature and research on scientific inquiry and nature of science in K-12 instruction. It is unique in its presentation of the distinctions and overlaps of inquiry and nature of science as instructional outcomes. The text would be appropriate for individuals preparing to become science teachers as well as experienced teachers. Researchers and teachers will find the text interesting as it carefully explores the subtleties and challenges of designing curriculum and instruction for integrating inquiry and nature of science.